Stability Considerations of Distributed Power Systems with Low Inertia Generators - Malhi, Emranjeet; Islam, Syed (Sultan Qaboos University, 2007)
This paper focuses on transient stability of synchronous generators in distributed generation power systems. Most of the generators used in distributed power generation systems have low inertia and high inductance. This creates rotor angle and frequency stability problems in the system. This paper consists of a stability study on a distributed power generation system and identification of the main stability problems faced by the system. This study conducted here is also helpful in identifying distribution generation limit in a power system.